The Relationship Between Sportsmanship and Motivation Among The Players to Professional Soccer Players In the West- Bank- Palestine - Mohammd Ibrahim Hih (My University, 2015)
The study aims to determine the level of sportsmanship and motivation among professional soccer players in west- bank and the relationship between them, in addition to determine the differences in the level of sportsmanship and motivation among professional soccer players in west- bank according to (degree of club, experience of professionalism, player’s position, player’s age, and type of participation in the team) variables. To achieve these purposes, the study was conducted on a random sample consisting of (197) professional soccer players in west- bank, the sample represents (37%) of the study population. For measuring the sportsmanship (Robert, etal, 1997) items scale was used, it was modified for 25 items to 24 items according to the specialist researcher opinions, and the scale was distributing into five domains (respect of social conventions, respect of rules and officials, full commitment, respect for opponent, and negative approach towards sports). To measure the motivation ( Alawi, 1998) Scale was used, consisting of 20 items and distributing into tow domains ( success performance and failure avoidance). In order to respond to study questions, means, percentages, standard deviation, pearson correlation coefficient, one way ANOVA and sidak post-hoc test were used. The results of the study revealed the following:  The level of sportsmanship amongst professional soccer players in west- bank was high, where the percentage of response was (71,8%), and it was high on all domains except the respect for opponent and the negative approach towards sports domains, the highest level was the respect of social conventions domain (78,8%), and the lowest level was the respect for opponent (61,2%).  The level of motivation amongst professional soccer players in west- bank was middle, where the percentage of response was (68,6%), and it was high on the success performance domain , where the percentage of response was (77,6%), and it was low on the failure avoidance domain, where the percentage of response was (59, 8%).  Furthermore the results showed that no significant statistical relationship (a= 0.05) between The sportsmanship and motivation amongst professional soccer players in west- bank, where the coefficient of pearson correlation was (0.10).  There were significant differences at (a= 0.05) in the level of sportsmanship due to the degree of club variable in favour of partial professional players on the negative approach towards sports, in addition , the differences were statistically significant according to the experience of professionalism variable in favour of 4- 6 years players , and according to the position of player variable in favour of centre player.  There were significant differences at (a= 0.05) in the level of motivation due to the degree of club variable in favour of total professional players on the success performance domain, where the results also showed that no significant differences at (a= 0.05) in the level of motivation due to the experience of professionalism, position of player, and age of player. Based on the findings of the study, the researcher recommended the players to engage in the sportsmanship, respect the rules and the sports regulations , avoid to harm the opponents, and accept the winning and losing from the side of coaches and administration. In addition to the importance of sports psychologist presence in the team staff. Key words: sportsmanship, motivation, West- bank, Palestin

هدفت الدراسة إلى تحديد العلاقة بين الروح الرياضية والدافعية لدى لاعبي كرة القدم المحترفين في الضفة الغربية والعلاقة بينهما, إضافة إلى تحديد الفروق في مستوى الروح الرياضية والدافعية لدى لاعبي كرة القدم للمحترفين في الضفة الغربية تبعا لمتغيرات درجة النادي والخبرة في الاحتراف و مركز اللاعب وعمر اللاعب ونوع المشاركة في الفريق, ولتحقيق ذلك أجْرِيَت الدراسة على عينة قوامها (197) لاعباً من لاعبي كرة القدم المحترفين في الضفة الغربية, وتم اختيارهم بالطريقة الطبقية العشوائية وتمثل ما نسبته تقريبا (37%) من مجتمع الدراسة. ولغاية قياس الروح الرياضية استخدِمَ مقياس روبرت وآخرون (Robert, etal, 1997) والمكون من (25) فقرة ولكن بعد تحكيمها من قبل المختصين اصبحت مكونة من (24) فقرة موزعة على خمسة مجالات هي: (مجال احترام التقاليد الاجتماعية ومجال احترام الانظمة والقوانين ومجال الالتزام الكامل بالمشاركة الرياضية ومجال الحرص على احترام المنافس ومجال النهج السلبي تجاه الرياضة), ولغاية قياس الدافعية استخدِمَ مقياس علاوي (1998) والمكون من (20) فقرة موزعة على بعدين هما:(انجاز النجاح, تجنب الفشل), ومن أجل الإجابة عن تساؤلات الدراسة استخدِمت المتوسطات الحسابية والنسب المئوية والانحراف المعياري ومعامل الارتباط بيرسون وتحليل التباين الاحادي واختبار (سيداك) للمقارنات البعدية وأظهرت النتائج ما يلي: - أنَّ المستوى الكلي للروح الرياضية لدى لاعبي كرة القدم للمحترفين الضفة الغربية كان عاليا, حيث وصلت النسبة المئوية للاستجابة الى (71.8%), وأن المستوى كان عاليا على جميع المجالات باستثناء مجال الحرص على احترام المنافس ومجال النهج السلبي تجاه الرياضة, وكان أعلى مستوى لمجال احترام التقاليد الاجتماعية (78.8%), وأقل مستوى لمجال الحرص على احترام المنافس (61.2%). - أنَّ مستوى الدافعية لدى لاعبي كرة القدم للمحترفين في الضفة الغربية كان متوسطاً على الدرجة الكلية حيث كانت النسبة المئوية للاستجابة (68.6%), وكان عالياً على مجال انجاز النجاح حيث كانت النسبة المئوية للاستجابة (77.6%), و منخفضاً على مجال تجنب الفشل حيث كانت النسبة المئوية للاستجابة (59.8%). - اظهرت النتائج أنَّه لا توجد علاقة دالة احصائيا عند مستوى الدلالة (α= 0.05) بين الروح الرياضية والدافعية لدى لاعبي كرة القدم للمحترفين في الضفة الغربية, حيث وصل معامل الارتباط (بيرسون) إلى (0.103). - كما وأظهرت النتائج أنَّهُ توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α= 0.05) في مستوى الروح الرياضية تعزى إلى متغير درجة النادي ولصالح لاعبي الاحتراف الجزئي على مجال النهج السلبي تجاه الرياضة, بينما كانت الفروق دالة إحصائياً تبعاً لمتغير الخبرة في الاحتراف ولصالح (4-6 سنوات ), وكانت الفروق أيضاً دالة إحصائياً تبعاً إلى متغير مركز اللاعب ولصالح لاعب الوسط. - وأظهرت النتائج كذلك وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α= 0.05) في مستوى الدافعية تعزى إلى متغير درجة النادي ولصالح اللاعبين المحترفين على مجال انجاز النجاح, بينما أظهرت أيضا أنه لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α= 0.05) في مستوى الدافعية تبعاً لمتغيرات الخبرة في الاحتراف و مركز اللاعب وعمر اللاعب. وأوصى الباحث بعدة توصيات منها التأكيد على اللاعبين بالتحلي بالروح الرياضية واحترام القوانين والأنظمة الرياضية وتجنب الحاق الأذى بالمنافسين وتقبل الفوز والخسارة من قبل المدربين والإدارة, وضرورة وجود أخصائي نفسي رياضي ضمن الجهاز الفني المسؤول عن الفريق. الكلمات الدالة : الروح الرياضية , الدافعية , الضفة الغربية , فلسطين .
العلاقة بين الروح الرياضية والدافعية لدى لاعبي كرة القدم المحترفين في الضفة الغربية – فلسطين